What are the effects of simulated muscle weakness on the sit-to-stand transfer?. Issue 11 (17th August 2020) - Caruthers, Elena J.; Schneider, Grant; Schmitt, Laura C.; Chaudhari, Ajit M. W.; Siston, Robert A.
Abstract: Populations with lower extremity muscle weakness have difficulty performing the sit-to-stand (STS) transfer. The degree of weakness that can be tolerated before compromising the ability to perform this task is unknown. Using dynamic simulations, we investigated the effects of weakness before changes in kinematics/kinetics would be required. Lower extremity muscles were weakened globally and individually and muscle forces were re-estimated as the model tracked original task kinematics/kinetics. The STS transfer was sensitive to quadriceps and plantarflexor weakness, suggesting that strengthening these muscles or changing kinematics are essential for populations who have difficulty rising from a chair independently.